Activity Report Section 1c / AO (Abwehr Officer) Headquarters, 20th Mountain Army for the time period January 1, 1943 through June 30, 1943. (1943)
Activity Report for the 20th Mountain Army. Taken from microfilm Records of the German Field Command, Armies, National Archives Series T-315, folder AOK 20 36560/16, first frame 000061. Translated by Major James F. Gebhardt, USA (retired).